Pulsão de morte na cultura: raízes e incidências - Bruno Curcino Hanke (2008)
The present study intends a quest for an understanding about the death drives feasible roots in culture. Three steps were done for that. The first one, to retake the psychoanalysis history in its dawn ambit give us possibilities to verify the uniqueness of this event in the end of XXcentury Viennian context. In that epoch, that coincides with the Austrian-Hungarian Empire wreck, the discipline created by Sigmund Freud presented precious enquiries about man and his relations with the other and himself although it was in agreement with many aspects ofimportant scientific ideas of its time. So, if Freuds care was to build a knowledge that could present a therapeutic efficiency for the treatment of human beings psyche, he gave it also a character of critics of culture. Researching points of some Freuds works that confirm theinterlacement between theoretical construction and a critic thought about culture, this dissertation indicates an explanation of the first driving theory, the narcissism concept and its ramifications. The narcissism concept advent presents the death theme of wich the obscurity in Freudian clinic appears and from wich we depart to death drive concept development and its discontent registrations. Accomplishing the study, understanding the meaning of the culture term in the context in wich psychoanalysis appears and the diference between that term and civilization term intends retake the death drive concept constitution. Its a controverted theme that take human educability to the limit. This study demonstrates which is in the dissipater death drive mark that it updates connection among subject, exterior world and language, bearing in mind the continual Eros and Thanatos action first one adding and second one cracking.